2022
DOI: 10.1159/000525494
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Osteoarthritis: A Mechanistic Review on the Present Documents

Abstract: <b><i>Background:</i></b> Osteoarthritis (OA), as one of the chronic debilitating conditions, affects 15% of people globally and is linked with serious problems, such as cardiovascular diseases, metabolic syndrome, and autoimmune inflammatory disorders. The current therapeutic options for this disease include nonsteroidal anti-inflammatory drugs, surgery, gene therapy, intrasynovial gel injection, and warm needle penetration. However, these approaches may be accompanied by considerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Quercetin is a avonoid compound that can exert anti-in ammatory and antioxidant effects in degenerative diseases. After administering quercetin to OA rats, Li et al found that the serum levels of proin ammatory cytokines were signi cantly reduced and that the production of ROS in chondrocytes was signi cantly reduced; furthermore, they con rmed that quercetin exerts these effects through the IRAK1/NLRP3 signalling pathway [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is a avonoid compound that can exert anti-in ammatory and antioxidant effects in degenerative diseases. After administering quercetin to OA rats, Li et al found that the serum levels of proin ammatory cytokines were signi cantly reduced and that the production of ROS in chondrocytes was signi cantly reduced; furthermore, they con rmed that quercetin exerts these effects through the IRAK1/NLRP3 signalling pathway [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, natural flavonoids can be divided into several sub-groups regarding the degree of oxidation in the central heterocycle, mainly including flavonols, flavones, flavanols/catechins, flavanones, anthocyanins, and isoflavones ( 14 ) ( Figure 1 ). Natural flavonoids have been demonstrated to have various biological activities, including anti-inflammation, anti-oxidation, anti-cancer, and bone protection ( 15 ). For example, xanthohumol (40 mg/day by intragastric administration for 8 weeks in mice and 10, 25, and 50 μM for cell culture) may exhibit inhibitory activity against the production of inflammatory cytokines and the expression of ECM catabolic enzymes by upregulating NRF2 and downregulating NF-κB pathways in vivo and in vitro ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that natural compounds positively treat and prevent diseases like Alzheimer's, osteoarthritis and inflammatory bowel disease. 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, adding some new agents to these pharmacological treatments or replacing a new agent with a different mechanism, such as alleviating oxidative stress, may be effective in treating COPD. Studies have shown that natural compounds positively treat and prevent diseases like Alzheimer's, osteoarthritis and inflammatory bowel disease 14–16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation